2019
DOI: 10.1007/s42452-019-1412-5
|View full text |Cite
|
Sign up to set email alerts
|

The engineered nanoparticles in food chain: potential toxicity and effects

Abstract: Nanomaterials include dispersing materials containing structural elements (grains, crystallites, blocks, clusters, etc.), due to their nano dimensions acquire qualitatively new functional and operational characteristics, offering several biomedical and technical advances over their bulk analogues. Taking into the consideration the fact that the impact of nanoparticles (NPs) to a living organism through the food chain is extremely important and have not been studied in detail yet, in this review we aimed to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 218 publications
(259 reference statements)
0
16
0
Order By: Relevance
“…1 . It has been reported that seed germination and seedling vigor are potentially induced in various crops upon nano-priming [ 7 , 8 , 9 ]. Moreover, this may be one of the best methods to sort out the dormancy problems and increase the germination of seeds in forest species (upland boreal), which indicates that nano-priming can be useful for forest reclamation purposes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 . It has been reported that seed germination and seedling vigor are potentially induced in various crops upon nano-priming [ 7 , 8 , 9 ]. Moreover, this may be one of the best methods to sort out the dormancy problems and increase the germination of seeds in forest species (upland boreal), which indicates that nano-priming can be useful for forest reclamation purposes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…43 Here, we focused on copper/copper oxide nanoparticles, which are used as "catalysts, magnetic storage media, solar energy transformers, solar cells, lithium batteries, semiconductors, field emission devices, gas sensors, biosensors in drug delivery, electronic chips, and heat transfer nanofluids". 37 Increasing research is being done to understand and manage the risks to the food chains, aquatic ecosystems, and microorganisms. 40,44,45 However, a comparative study on the cytotoxicity of copper nanoparticles in prokaryotic and eukaryotic cells is not available.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With growing production and applications of nanometer-sized materials, considerations should be taken so that the nanoparticle material is safe for use and, of arguably equal importance, can safely be disposed of. While many nanoparticles are tested for human contacts, such as in wound healing agents, food, sunscreens, disinfectants, and biosensors for drug delivery, many are produced with little or no information about their biocompatibility . Furthermore, it is also not always required to disclose nanoparticles as ingredients …”
Section: Resultsmentioning
confidence: 99%
“…The chemical methods of nanoparticle synthesis are the most common approaches commercially employed in various areas of NP applications. Concurrently, plenty of research indicates a potential environmental threat of nanotechnology related to NP toxicity [111][112][113][114][115]. The chemical approach to NP synthesis is related to the use of toxic chemicals, which are hazardous to humans and the environment [116].…”
Section: Selenium Nanoparticles In Animal Nutritionmentioning
confidence: 99%